نظریہ وحدۃ الوجود‘اسلامی تعلیمات کی روشنی میں; ایک تجزیاتی مطالعہ’: The Concept of Wahda-Tul-Wujood in the light of Islamic Education; an analytical study - akram , Dr. Muhammad; Muhammad saad , Muhammad saad (Al-Amīr Research Journal for Islamic Studies, 2023)
Thinkers expressed their opinion about the position and relationship between the universe and the Creator the universe. In various schools of thoughts, the sufia explained the relationship between the Creator and the creations as the ideology of “Wahda-Tul-Wujood”. The critics consider this ideology of wahda-tul-wojood as “Infidelity”. The critics of tasawuf and sufia’ arguments will be analyzed in the light of Islamic educations. According to the critics of the tasawuf, the sufia consider everything as Allah. They think everything is Allah. Allah is Allah and even man is also Allah. Reality of wahda-tul-wojood is adopted and presented by Ibn-e-Arabi. Wahda-Tul-Wojood will be analyzed in the light of Islamic education. Key Words: Wahda-Tul-Wujood, Mysticism, Ibn-e-Arbi, Philosphers, Islamic point of view.